2018
DOI: 10.2478/cerce-2018-0012
|View full text |Cite
|
Sign up to set email alerts
|

Germination, Growth and Yield Performance of Flax (Linum usitatissimum L.) Under Gamma Irradiation Stress

Abstract: Gamma irradiation is a widely manipulated mutation breeding approach in agriculture for producing crops with desired agronomic traits. The technique is particularly advantageous to conventional breeding methods because of minimal labor and time requirement. Under laboratory and field experiments during 2013, seeds of Linum usitatissimum L. were irradiated with 2, 4, 8, 12, 16, 20, 24, 28 and 32 krad of gamma irradiation doses from Co-60 source for evaluating their effects on germination, seedling survival, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Results of Table ( 7) indicated that gamma rays had a significant effect on the Leaves ratio, as the plants irradiated at the level of 9 Gy gave the highest average of this trait amounted to 21.46%, and the percentage decreased with the increase in the level of rays, and the plants irradiated at the level of 27 Gy gave the lowest Leaves ratio percentage (19.86%), and the reason for this may be attributed to the decrease in the dry weight of the leaves as a result of the inhibition of gamma rays of the hormone ethylene, which contributes to the support and growth of leaves, and this results are in line with the results of Ali et al, (2018) and Naz et al, (2019). results of the same table showed a significant effect of the genotypes on this trait, as the Sakha5 genotype outperformed all the genotype, achieving the highest average of this trait amounted to 21.48%, while the Sakha6 genotype gave the lowest average of 19.49%, and the reason for the discrepancy of this trait may be due to the increase In the height of the plant.…”
Section: Table (3) Analysis Of Variance For the Studied Traitssupporting
confidence: 85%
See 1 more Smart Citation
“…Results of Table ( 7) indicated that gamma rays had a significant effect on the Leaves ratio, as the plants irradiated at the level of 9 Gy gave the highest average of this trait amounted to 21.46%, and the percentage decreased with the increase in the level of rays, and the plants irradiated at the level of 27 Gy gave the lowest Leaves ratio percentage (19.86%), and the reason for this may be attributed to the decrease in the dry weight of the leaves as a result of the inhibition of gamma rays of the hormone ethylene, which contributes to the support and growth of leaves, and this results are in line with the results of Ali et al, (2018) and Naz et al, (2019). results of the same table showed a significant effect of the genotypes on this trait, as the Sakha5 genotype outperformed all the genotype, achieving the highest average of this trait amounted to 21.48%, while the Sakha6 genotype gave the lowest average of 19.49%, and the reason for the discrepancy of this trait may be due to the increase In the height of the plant.…”
Section: Table (3) Analysis Of Variance For the Studied Traitssupporting
confidence: 85%
“…working to increase its linen productivity in the unity of the area is what the plant breeders seek, and that is through the introduction of the advanced technologies in the production, the selection for the desired traits after using mutations, where mutation causes genetic variation that gives the breeder the opportunity to intervene to select the useful genotype, One of the means of physical mutagenicity is the use of (gamma rays), and the effect of doses depends on the type and strain of the plant in the first place, as some plants are stimulated by low doses of gamma rays, while other plants are stimulated by high doses, (Youssef, 2018). Among the previous studies that dealt with physical mutagenesis are the study of Alka (2013), Bornare et al, (2013) and Ali et al, (2018) that they studied the effect of gamma rays on the field characteristics of flax crop. The main purpose of flax breeding is to develop promising varieties that would outperform the existing ones in yield and quality characteristics.…”
mentioning
confidence: 99%
“…According to Kim et al (2004) 2017), these effects include modi cations to the plant's cellular structure and metabolism, such as thylakoid membrane enlargement, changes in photosynthesis, modulation of the antioxidative system, increase in enzyme activity, and accumulation of phenolic compounds. According to recent researches, gamma radiation at lower doses can successfully increase the germination rate (Ali et al, 2018) and enzyme activity (Lopes et al, 2017;Rizki et al, 2019). Additionally, some bene cial impacts on total phenolic content, protein, seed weight, and germination have been documented (Hanafy & Akladious, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These impacts include changes in the plant's cellular structure and metabolism, such as thylakoid membrane expansion, photosynthetic modi cations, antioxidative system regulation, and phenolic compound accumulation (Kim et al, 2004;Wi et al, 2005;Ikram et al, 2010). Recently, it has been reported that lower doses of gamma radiation effectively increase enzyme activity (Lopes et al, 2017) and seed germination rate (Ali et al, 2018). Some positive effects have also been reported on rapid germination, seed weight, protein, and total phenolic contents (Hanafy & Akladious, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Melki and Marouanig (2010) studied the effect of levels from gamma rays (0, 10, 20, 30 Gy) on wheat germination and seedling growth in greenhouse conditions; they found a development in the number and length of roots by 18 and 32% respectively at dose 20 Gy 14 . Under laboratory conditions and field of experiment, were planted flax seeds irradiated with different doses by using 60 Co (cobalt element); it was noted that doses up to 8 Kr were favorable in stimulating growth through the occurrence of significant differences in seed germination, branch length, the number of leaves and leaf area while the higher dose of 8 Kr led to a negative effect on germination 15 .…”
Section: Introductionmentioning
confidence: 99%